The simple microsegregation model for steel considering MnS formation in the liquid and solid phases - Dali You; Christian Bernhard; Michael Bernhard; Susanne Katharina Michelic (Journal of Materials Research and Technology, 2024)
A simple microsegregation model for steel considering MnS formation in the liquid and solid phases is proposed. The concentration of the solutes during the solidification is calculated using the discretized Scheil-Gulliver model for steel (SGS). In the calculation, the planar dendrite is divided into a finite number (n) of elements to record the local solid concentrations and calculate the mass fraction of MnS precipitation during further cooling. The solidification part of the model is validated by measured solidification temperatures and the MnS formation amount predicted by the FactSage thermochemical software. The model was applied to evaluate the high-temperature ductility of the selected steel. The optimum Mn content of the assumed steel was obtained based on the simulation.